Evaluasi Gerakan Literasi Sekolah di Sekolah Dasar dengan menggunakan Model Evaluasi CIPPO - Parera, Stasia Veronica; Ade Iriani; Marinu Waruwu (Kelola: Jurnal Manajemen Pendidikan, 2024)
The purpose of this study is to evaluate the school literacy initiative program at SD Kristen 03 Eben Haezer Salatiga. This research is evaluative and uses the CIPPO model. Data collection techniques include interviews, observations, and documentation. The validity of the research data is tested for credibility using triangulation techniques, which consist of source triangulation and technical triangulation. Data analysis involves description, reduction, display, and drawing conclusions. The results based on the context aspect show that the literacy initiative program (GLS) is essential. Regarding the input aspect, the GLS program meets the school's needs in addressing low student literacy skills and is supported by adequate human resources, budget, and infrastructure. In the process aspect, the GLS program was carried out well according to the plan, although some teachers need reminders about the SOP. The product of the GLS program implementation includes improvements in students' reading ability, reading comprehension, and writing skills. This is evidenced by students’ works, such as writing competitions, poetry, friendship stories, and creating clippings about earth's surface features and the environment. The outcome or impact of the results is that students gain new knowledge and vocabulary, become creative and innovative, and are able to develop their imagination by writing poetry and short stories. Additionally, students become more confident in presenting their own work.